Biological properties of the compounds formed by the combination of the 1,2,4-triazoles, furans and other functional substitutes - D. M. Danilchenko; V. V. Parchenko; O. I. Panasenko; Ye. G. Knysh (Zaporozhye State Medical University, 2015)
Aim. To study biological properties of the compounds formed by the combination of the 1,2,4-triazoles, furans and other functional substitutes. Methods and results. It is known that 1,2,4-triazole heterocyclic system is promising for creation of new biologically active molecules. The entire series of drugs, the active ingredient of which is a derivative of the 1,2,4-triazole (fluconazole, ribavirin, avesstim, trifuzol and others) has entered in the practice of modern medicine, pharmacy and veterinary medicine. Special attention to the creation of potential drugs deserves the opportunity of combining fragments of 1,2,4-triazole, the "nucleus" of furan and other substitutes. Literary sources show different types of pharmacological activity of the compounds formed by such "symbiosis". Subsequent chemical transformations of these structures contribute to the establishment of consistent pattern between the structure and biological activity of the corresponding 1,2,4-triazole derivatives, and this in turn has positive effect on the most rapid identification of the most promising classes of compounds. Conclusion. Despite the huge number of publications devoted to the study of the biological properties of the 1,2,4-triazole derivatives with furan fragment, there is no systematization of the results of these research.